Anatomical description of arterial segment of spleen of deer - Melo, Alan Perez Ferraz; Souza, Wilson Machado de [UNESP]; Rodrigues, Rosangela Filipe; Alves, Flavio; Guerra, Ricardo; Rici, Rose; Favaron, Phelipe; Miglino, Maria Angélica; Dio, L. John Aphonso Di (Wiley, 2011)
The anatomosurgical segmentation of the arteries of the spleen was studied in 31 deer of the species Mazama gouazoubira and Blastocerus dichotomus by means of vascular injection with latex and vinyl acetate and radiographic examination. The arteria lienalis penetrated through the hilus lienis in 87% of the cases, whereas an extrahilar artery was present in the other cases. An extraparenchymal division of the lineal artery into two, three or four segmental arteries was observed in 74% of the cases. Anastomoses between intraparenchymal arterial branches were rare and of a reduced calibre.
Keywords: Segmentos; Baco; Cervo; Arteria lienal